Security, Privacy, and Applied Cryptography Engineering Second International Conference, SPACE 2012, Chennai, India, November 3-4, 2012, Proceedings - Bogdanov, Andrey.; Bogdanov, Andrey.; Sanadhya, Somitra.; Sanadhya, Somitra. (Security and Cryptology, 2012)
This book constitutes the refereed proceedings of the Second International Conference on Security, Privacy and Applied Cryptography Engineering held in Chennai, India, in November 2012. The 11 papers presented were carefully reviewed and selected from 61 submissions.  The papers are organized in topical sections on symmetric-key algorithms and cryptanalysis, cryptographic implementations, side channel analysis and countermeasures, fault tolerance of cryptosystems,  physically unclonable functions, public-key schemes and cryptanalysis, analysis and design of security protocol, security of systems and applications, high-performance computing in cryptology and cryptography in ubiquitous devices.